1986
DOI: 10.1161/01.cir.74.2.367
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of dobutamine and amrinone on myocardial contractility and ventricular performance in patients with severe heart failure.

Abstract: The effects of amrinone, dobutamine, and a combination of the two drugs on peak positive left ventricular dP/dt and left ventricular performance were evaluated in 11 patients with chronic congestive heart failure. When administered alone, both dobutamine (10.9 gg/kg/min) and intravenous amrinone (1.9 mg/kg/min) significantly increased left ventricular dP/dt and performance. When compared with dobutamine alone, the addition of amrinone resulted in further increases in left ventricular dP/dt and cardiac index (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(23 citation statements)
references
References 17 publications
2
20
0
1
Order By: Relevance
“…Only one other study has addressed this important issue in vivo in patients with CHF (35). Our data and conclusion are consistent with those of Gage et al (35) who showed that the +dP/dt response to intravenous dobutamine was greater in the presence of intravenous amrinone. In addition, the IC infusion method allows two further conclusions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Only one other study has addressed this important issue in vivo in patients with CHF (35). Our data and conclusion are consistent with those of Gage et al (35) who showed that the +dP/dt response to intravenous dobutamine was greater in the presence of intravenous amrinone. In addition, the IC infusion method allows two further conclusions.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, the positive inotropic response of guinea pig papillary muscle to isoproterenol is potentiated when isoproterenol is given at the peak of a minimally effective concentration of milrinone or after prolonged incubation with milrinone (34). Only one other study has addressed this important issue in vivo in patients with CHF (35). Our data and conclusion are consistent with those of Gage et al (35) who showed that the +dP/dt response to intravenous dobutamine was greater in the presence of intravenous amrinone.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Gage et al [14] demonstrated that amrinone and dobutamine had additive effects on left ventricular function in patients with congestive heart failure. Similar observations were made with other phosphodiesterase inhibitors [15].…”
Section: Combination Of Phosphodiesterase Inhibitors With Adrenergic mentioning
confidence: 99%
“…Se não há muitas dúvidas sobre seu valor na terapêuti-ca dos quadros descompensados [1][2][3][4][5] , o mesmo não ocorre quando da sua prescrição de maneira crônica para pacientes compensados [6][7][8][9] . A sua prescrição, quando e como, vem sendo objeto de vários artigos e é motivo de intensa controvérsia, o que nos induziu a expor nosso ponto de vista sobre tema tão importante.…”
unclassified